Single‐cell study of neural stem cells derived from human iPSCs reveals distinct progenitor populations with neurogenic and gliogenic potential. (17th November 2019) - Lam, Matti; Sanosaka, Tsukasa; Lundin, Anders; Imaizumi, Kent; Etal, Damla; Karlsson, Fredrik H.; Clausen, Maryam; Cairns, Jonathan; Hicks, Ryan; Kohyama, Jun; Kele, Malin; Okano, Hideyuki; et al.
Abstract: We used single‐cell RNA sequencing (seq) on several human induced pluripotent stem (iPS) cell‐derived neural stem cell (NSC) lines and one fetal brain‐derived NSC line to study inherent cell type heterogeneity at proliferating neural stem cell stage and uncovered predisposed presence of neurogenic and gliogenic progenitors. We observed heterogeneity in neurogenic progenitors that differed between the iPS cell‐derived NSC lines and the fetal‐derived NSC line, and we also observed differences in spontaneous differentiation potential for inhibitory and excitatory neurons between the iPS cell‐derived NSC lines and the fetal‐derived NSC line. In addition, using a recently published glia patterning protocol we enriched for gliogenic progenitors and generated glial cells from an iPS cell‐derived NSC line. Abstract : Single‐cell RNA sequencing on neural stem cell (NSC) lines showed inherent cell type heterogeneity for neurogenic and gliogenic progenitors. Induced pluripotent stem (IPS) cell‐derived NSC lines and fetal‐derived NSC line showed differences in spontaneous differentiation outcome for inhibitory and excitatory neurons. iPS cell‐derived NSCs hold enrichment potential for gliogenic progenitors.